AN ANALYTICAL STUDY ON THE RELATIONSHIP BETWEEN NUTRITIONAL LITERACY AND ADHERENCE TO DIETARY PROTOCOLS AMONG INDIVIDUALS WITH DIABETES IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Diabetes mellitus, a growing public health challenge in Nigeria, demands effective dietary management to mitigate complications. This study investigates the relationship between nutritional literacy and adherence to dietary protocols among individuals with type 2 diabetes in Cross River State, Nigeria. A cross-sectional design was employed, utilizing a structured questionnaire and 24-hour dietary recall to collect primary data from 384 participants across urban and rural communities. Nutritional literacy was assessed using a validated Nutrition Literacy Assessment Instrument, while adherence was measured via the Dietary Adherence Scale. Findings revealed that 42.7% of participants had adequate nutritional literacy, with higher literacy levels in urban areas (OR = 1.62, 95% CI: 1.12–2.34). Adherence to dietary protocols was low (36.2%), with significant associations between nutritional literacy and adherence (p < 0.001). Socio-demographic factors, including education (p = 0.002), income (p = 0.015), and urban residence (p = 0.008), influenced both literacy and adherence. Barriers such as cultural food preferences and limited access to healthy foods were identified. The study underscores the need for targeted nutrition education interventions to enhance dietary adherence and improve health outcomes. Recommendations include integrating nutrition literacy programs into diabetes care and addressing socio-economic barriers to healthy eating.